The design and development of peer-to-peer based mobile application for petty trading - Ishak, Iskandar; Sidi, Fatimah; Mohd. Sani, Nor Fazlida; Affendey, Lilly Suriani; Ariffin, Ahmad Alauddin; Mazli, Raedi Fizuwan (Asian Research Publishing Network, 2013)
Recent popularity of mobile devices such as smart phones and tablets have increase the usage of these devices including by petty traders. This paper presents a prototype mobile phone application designed and developed to enhance the business activities for petty traders especially in open markets such as night markets. The proposed application consists of three major component for petty trading activities: i)Trader Searching Component, ii)Trader- Customer Communication Component, and iii)Trader Pamphlet Distributor. Provided that both the trader and customer have installed the application on their phones the application will provide real-time information to the customer regarding nearest available traders doing their businesses at a particular trading place visited by the customer. It has to be noted that the application is based on decentralized peer-to-peer architecture in which there is no centralized party managing all the data.